Investigating the Role of Tax Consultant in Urgencies of Voluntary Disclosure Program 2022 - Merawati, Luh Komang; Endiana, I Dewa Made; Suardyana, Luh Kalpika Jyunda A. (Kompartemen : Jurnal Ilmiah Akuntansi, 2023)
The government has made numerous attempts to raise tax revenues in response to the Covid 19 outbreak, either by enhancing or perfecting tax laws. The Voluntary Disclosure Program (PPS) is one of the government's policies. PPS is sometimes referred to  Tax Amnesty Volume II. This study intends to investigate the influence of PPS policy on perceptions of taxpayer compliance and the function of tax consultants as a moderating factor. Primary data were collected randomly through the distribution of online questionnaires and obtained 33 respondents as samples. The data analysis technique used is the Moderated Regression Analysis (MRA) interaction test. The test results prove that the PPS policy has a positive effect on the perception of taxpayer compliance and the role of the Tax Consultant is proven as a moderating variable that strengthens the relationship. The results of the study are expected to provide an empirical contribution to the taxation policies taken by the government so that they can be used as evaluation materials to innovate and educate the public in improving tax compliance and state revenues.